Motivation- based digital mindfulness sati in reducing screen addiction in the era of social media: a systematic literature review - Damana, I Ketut (Insan Akademika Publications, 2025)
The problem is that not many people know the right mindfulness. This study aims to examine the role of sati-based digital mindfulness in reducing screen addiction in the era of social media. Amid the increasing use of digital devices and the dominance of social media in everyday life, the phenomenon of screen addiction has become a significant mental health issue. This study uses a systematic literature approach to explore and analyze empirical findings from various relevant previous studies, with a focus on the application of the concept of mindfulness (sati) rooted in Buddhist practice in the modern digital context. The applied method used involves the identification, selection, and critical analysis of published scientific articles limited to the last ten years from various academic databases and the number of 8 articles analyzed and the framework used to strengthen the validity of the method . The results of the study indicate that sati-based digital mindfulness can reduce impulsive screen use, increase self-awareness of digital behavior patterns, and improve the balance between online and offline life. In addition, sati-based interventions have been proven effective in building healthy digital habits through self-reflection and emotional control. In conclusion, mindfulness-based digital mindfulness has potential as a preventive and rehabilitative approach in addressing screen addiction, as well as practical contributions and originality of findings in the form of mindfulness integrated into digital education programs and broader psychological interventions.